THE CHARACTER DEVELOPMENT OF ‘BEN’ IN GIFTED HANDS: THE BEN CARSON'S STORY THROUGH ERIKSON'S PSYCHOSOCIAL THEORY - AGM, Cicilia Angelis; Miranti, Ira; Dwiastuty, Nina (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2019)
This study aims to identify and provide a description of the development of the main character in the film Gifted Hands: The Ben Carson Story by Thomas Carter based on the approach of textual literary psychology through qualitative descriptive techniques, namely listening, observing, and copy-writing. Erikson's theory of psychological development, which reviews the development of the character influenced by those who are nearby becoming the focal point of the discussion - in terms of dialogue, action-reaction, and the situation depicted in the film. The findings in this study are four stages of character development from eight stages, namely school age, adolescence, early adulthood, and adulthood, at each stage, there are two elements namely dystonic (disruptive) and syntonic (harmony).